THE EFFICACY OF HONEY AS AN ALTERNATIVE TO STANDARD ANTISEPTIC CARE IN THE TREATMENT OF CHRONIC PRESSURE ULCERS AND DIABETIC FOOT ULCERS IN ADULTS - PEREIRA, GF; BALMITH, M; NELL, M (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: A chronic wound fails to progress through the phases of wound healing in an orderly and appropriate process, and poses a major challenge to wound care professionals. Pressure ulcers (PUs) and diabetic foot ulcers (DFUs) are classified as chronic wounds. Antiseptics, such as povidone-iodine (PVP-I), are often used to treat bacterial infections in chronic wounds; however, their efficacy and ability to accelerate wound healing has come into question. As a result, current medical research is now focusing on alternative and natural antiseptic agents, such as honey, for the treatment of chronic wounds. The aim of this study was to analyze the wound healing effects of honey in PU and DFU treatment in comparison to standard antiseptic care. Methods: A systematic literature search of PubMed, ScienceDirect, and ClinicalKey was conducted to identify all published data of clinical trials and narrative reviews that investigated or reported the use of honey and standard antiseptics in the treatment of PUs and DFUs in adults. A keyword search was then performed using the following keywords: “PUs”, “DFUs”, “antiseptics”, “PVP-I”, “honey”, “Manuka honey (MH)”, and “wound healing”. Database restrictions were implemented based on the inclusion and exclusion criteria, notably the report’s availability, completion status and language, the sample populations’ age, as well as, the date of publication. A preferred reporting item for systematic review and meta-analysis (preferred reporting items for systematic reviews and meta-analyzes) diagram was constructed illustrating the study selection process. The eligibility of articles was assessed by the screening of titles, abstracts and full texts. A total of 12 articles were included in this study comprising of 775 patients with PUs, DFUs or a combination of PUs and DFUs. Results: Results indicated that honey reduced bacterial infection, reduced pain and edema experienced by patients, reduced the odor of the wound and promoted wound healing in the treatment of chronic ulcers. Honey was also found to be effective in the process of debridement and exudate removal. Conclusion: Honey was found to be highly effective in the treatment of PUs and DFUs and should be considered as an alternative to standard antiseptic care in the treatment of chronic wounds. However, the literature in this study is limited and so further research into honey and its antiseptic-promoting activity in wound healing is recommended.